Multiparadigm Programming in Industry: A Discussion with Neal Ford and Brian Goetz - Wampler, D; Clark, T; Ford, N; Goetz, B (IEEE software, 2010)
Using multiparadigm programming (MPP) has costs as well as benefits. Over email, guest editors Dean Wampler and Tony Clark discussed with Neal Ford and Brian Goetz the practical issues for MPP in industrial software development teams. What follows is a transcript.